2013
DOI: 10.1016/j.atmosenv.2013.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Saharan dust transport into the Mediterranean basin with CMAQ

Abstract: HIGHLIGHTS• A dust emission module has been implemented in the WRF-SMOKE-CMAQ modelling system.• The system has been applied and evaluated for Saharan dust outbreaks into Europe.• Contributions up to 14 ng rrT 3 to 24-h PMio concentration were predicted in Spain.• Global R-value for ground-level PMio increased from 0.33 to 0.48.• Good agreement with satellite products although AOD is underestimated. ABSTRACTThe need for a better quantification of the influence of Saharan dust transport processes on the air qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 51 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Information about the vertical structure of the dust episode and vertical behaviors of the atmospheric conditions is provided from attenuated backscatter profiles at 532 nm retrieved from the spaceborne Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) on board the CALIPSO together with its 60 m and 12 km vertical and horizontal resolutions, respectively. From the literature, numerous studies investigated the vertical structure of the Saharan dust outbreaks by using CALIPSO observations for Mediterranean Basin (e.g., [24][25][26]) and for Turkey [21]. In this study, CALIPSO observations for 23 March.…”
Section: Black Seamentioning
confidence: 99%
“…Information about the vertical structure of the dust episode and vertical behaviors of the atmospheric conditions is provided from attenuated backscatter profiles at 532 nm retrieved from the spaceborne Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) on board the CALIPSO together with its 60 m and 12 km vertical and horizontal resolutions, respectively. From the literature, numerous studies investigated the vertical structure of the Saharan dust outbreaks by using CALIPSO observations for Mediterranean Basin (e.g., [24][25][26]) and for Turkey [21]. In this study, CALIPSO observations for 23 March.…”
Section: Black Seamentioning
confidence: 99%
“…During the MINOS campaign (Mediterranean Intensive Oxidant Study; Lelieveld et al, 2002) over the same region, Roelofs et al (2003) reported ozone concentrations in altitude of about 50 ppb, with peaks reaching 120 ppb. Lidar observations of ozone undertaken during the ESCOMPTE campaign (Expérience sur site pour contraindre les modèles de pollution atmosphérique et de transport d'émissions; Cros et al, 2004), in summer in the western part of the Mediterranean showed that highly concentrated plumes may be formed over a given country and transported for several hundreds of kilometers, before reaching ground levels (Colette et al, 2006). Aerosols are also highly variable in space, time and composition.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ozone was simulated using the CHIMERE regional CTM during the ESCOMPTE campaign (Menut et al, 2005) and the summertime ozone maximum was analyzed using the TOMCAT global CTM (Richards et al, 2013). Aerosol observations in the Mediterranean area often show large contributions from mineral dust, so that numerous studies were devoted to this species (Pérez et al, 2011;Nabat et al, 2012;Menut et al, 2013b;de la Paz et al, 2013). Their impact on climate via their radiative effect was recently analyzed with the models COSMO (Vogel et al, 2009), RegCM (Santese et al, 2010), SKYRON (Spyrou et al, 2013) and ALADIN-Climate .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…WRF-CMAQ has significant improvements especially for suspended particulate matter. D. Paz et al [24] combine dust emission module (DEM) with CMAQ and implements WRF-SMOKE-SMAQ system to increase the correlation degree between observed and modeled PM 10 concentrations. Han et al [25] obtain an in-depth understanding of the relationship between regional low visibility and aerosol particles based on Regional Atmospheric Modeling System (RAMS)-CMAQ.…”
Section: Related Workmentioning
confidence: 99%